Enhancing social participation in young people with communication disabilities living in rural Australia: outcomes of a home-based intervention for using social media. (August 2015) - Raghavendra, Parimala; Newman, Lareen; Grace, Emma; Wood, Denise
Abstract Purpose: The purpose of this study is to investigate the effectiveness of a home-based intervention using social media to enhance social networks of young people with disabilities and communication difficulties. Method: Eight young people (Mage = 15.4 years) with communication disabilities participated from two rural Australian towns. The intervention provided assistive technology and training to learn social media use. A mixed-method design combined pre- and post-assessments measuring changes in performance, satisfaction with performance, attainment on social media goals, and social network extension, and interviews investigated the way in which the intervention influenced social participation. Results: Participants showed an increase in performance, and satisfaction with performance, on the Canadian Occupational Performance Measure; paired t-tests showed statistical significance at p <0.01. Wilcoxon Signed Ranks revealed a significant increase in the number of online communication partners, p <0.05. The interviews highlighted participants' and parents' perceptions of increased social connections, improved communication frequency and nature, and speech intelligibility and literacy as a result of the intervention. Conclusions: The findings suggest that learning to use social media leads to increase in social participation among rural-based young people with communication disabilities. In order to benefit from advantages of learning to use social media in rural areas, parents and service providers need knowledge and skills to integrate assistive technology with the Internet needs of this group. Implications for Rehabilitation Young people with communication disabilities living in rural areas of Australia can learn and benefit from using social media such as Skype, e-mail, and Facebook to enhance their social connections. For young people with communication disabilities to benefit from social media, there needs to be more collaboration between home and school with use of assistive technologies, training, and support to learn to use social media. Parents/caregivers living in rural areas need support and training in using social media, knowledge of assistive technologies, and the expectations that these can benefit their children. Disability service providers need knowledge and skills to integrate social media and assistive technology for their clients.